Colo. Rev. Stat. ch. 84, art. III, § 1 (1867) - (:unkn) unknown (My University, 1868)
Authorized the board of trustees of every town to provide regulations for the storage of gunpowder, gun-cotton, nitro-glycerine, tar, pitch, resin, and other combustible or inflammable materials, and to prescribe the places and manner of storing the same.
Keywords: GUNPOWDER - STORAGE